2022
DOI: 10.1017/s0022215121004485
|View full text |Cite
|
Sign up to set email alerts
|

Functional endoscopic sinus surgery outcome in chronic rhinosinusitis patients with hypoplastic maxillary sinus

Abstract: Objective To review the clinical characteristics, prevalence and outcomes of chronic rhinosinusitis patients with a hypoplastic maxillary sinus who underwent functional endoscopic sinus surgery. Methods A retrospective review was performed for the 814 consecutive, elective functional endoscopic sinus surgery procedures performed at an academic centre from 2010 to 2020, to identify patients with a hypoplastic maxillary sinus. Result A total of 56 hypoplastic maxillary si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These positive outcomes of FESS are common among Middle Eastern CRS patients. Al-Qudah et al [ 10 ] investigated another group of 78 patients and reported that FESS significantly improved the symptoms of CRS. Through self-reported data, the researchers found that patients significantly improved their QOL post-surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These positive outcomes of FESS are common among Middle Eastern CRS patients. Al-Qudah et al [ 10 ] investigated another group of 78 patients and reported that FESS significantly improved the symptoms of CRS. Through self-reported data, the researchers found that patients significantly improved their QOL post-surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Through self-reported data, the researchers found that patients significantly improved their QOL post-surgery. The study also reported a low complication rate and no significant adverse events [ 10 ].…”
Section: Introductionmentioning
confidence: 99%